Play, Playfulness, and Self-Efficacy: Parental Experiences with Children on the Autism Spectrum - Rosa Román-Oyola; Verónica Figueroa-Feliciano; Yoliannie Torres-Martínez; Jorge Torres-Vélez; Keyshla Encarnación-Pizarro; Samariz Fragoso-Pagán; Luis Torres-Colón (Hindawi-Wiley, 2018)
Background. Play serves as an essential medium for parent-child interaction; however, engaging children with ASD through play can be a challenge for parents. Purpose. The purpose of this phenomenological study was to explore the perspectives of parents with children on the autism spectrum regarding play experiences and self-efficacy during play encounters. Method. Semistructured interviews were administered to 8 parents of children 3-7 years of age with ASD. The analysis was guided by the constant comparison method. Findings. Parental narratives denoted playful experiences reflecting components of Skard and Bundy's model of playfulness. The facilitation of framing and suspension of reality were generally more challenging than facilitating intrinsic motivation and internal control. Participants associated self-efficacy during play with their perceived ability to interact with their child and with positive emotions experienced during play. Fathers generally derived a greater sense of self-efficacy from play encounters than mothers, and this was explained by differences in fathers' and mothers' motivations for playing. Mothers were motivated to play for outcome-oriented reasons (e.g., promote the child's progress) whereas fathers' motivations depicted greater emotional emphasis, reflecting a better match between motivation and perceived indicators of efficacy during play. Conclusion. The results suggest that a good match between motivation for playing and perceived indicators of efficacy during play is important for a parental sense of self-efficacy. Occupational therapists should utilize coaching strategies to increase parents' understanding of play and playfulness and how they can affect a sense of parental self-efficacy.